2010
DOI: 10.5194/acp-10-2709-2010
|View full text |Cite
|
Sign up to set email alerts
|

Particle characterization at the Cape Verde atmospheric observatory during the 2007 RHaMBLe intensive

Abstract: Abstract. The chemical characterization of filter high volume (HV) and Berner impactor (BI) samples PM during RHaMBLe (Reactive Halogens in the Marine Boundary Layer) 2007 shows that the Cape Verde aerosol particles are mainly composed of sea salt, mineral dust and associated water. Minor components are nss-salts, OC and EC. The influence from the African continent on the aerosol constitution was generally small but air masses which came from southwestern Europe crossing the Canary Islands transported dust to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 58 publications
9
55
0
Order By: Relevance
“…The solution was left to evaporate at about 100 • C and thereafter the substrates containing the particles on the foils were measured. As reported by Müller et al (2010), the cut foil diameters were typically 6 mm and were close to the TXRF beam diameter of 10 mm. However, due to sample orientation on the substrate, samples were measured at two different angles having a difference of 90 • between them in order to ensure a complete excitation of the particle spots.…”
Section: Metal Analysismentioning
confidence: 70%
“…The solution was left to evaporate at about 100 • C and thereafter the substrates containing the particles on the foils were measured. As reported by Müller et al (2010), the cut foil diameters were typically 6 mm and were close to the TXRF beam diameter of 10 mm. However, due to sample orientation on the substrate, samples were measured at two different angles having a difference of 90 • between them in order to ensure a complete excitation of the particle spots.…”
Section: Metal Analysismentioning
confidence: 70%
“…Clearly, in the atmosphere, spatial and temporal variations in DF could have a significant impact on the observed BrO distribution. In a recent application of the model to the tropical Atlantic (O'Brien et al, 2009), the model failed to reproduce the high BrO (2-3 ppbv) observed there, which could be partly explained by the low DF used in the model, as recent observation indicates that the sea salt bromine near Cape Verde is heavily depleted (Müller et al, 2010). It is clearly necessary to work towards including a detailed sea salt microphysical-chemical module to study bromine chemistry at the global scale.…”
Section: Results and Analysismentioning
confidence: 99%
“…Additionally, it was assumed that 10-15 % of the total mass was water. Weighing and the chemical analyses of the impactor samples were carried out according to the methods described in Müller et al (2010). The foils were stored in a refrigerator and transportation was done using cryogenic boxes below −10 • C to avoid chemical processing of organic material.…”
Section: Mass Concentration Using the Gravimetrical Methods (M Gr )mentioning
confidence: 99%